Caesar in Gaul and Rome : war in words - Riggsby, Andrew M. (University of Texas Press, 2006)
"Anyone who has even a passing acquaintance with Latin knows 'Gallia est omnis divisa in partes tres' ('All Gaul is divided into three parts'), the opening line of De Bello Gallico, Julius Caesar's famous commentary on his campaigns against the Gauls in the 50s BC. But what did Caesar intend to accomplish by writing and publishing his commentaries, how did he go about it, and what potentially unforeseen consequences did his writing have? These are the questions that Andrew Riggsby pursues in this fresh interpretation of one of the masterworks of Latin prose. Riggsby uses contemporary literary methods to examine the historical impact that the commentaries had on the Roman reading public.